On free vibrations of a thick periodic junction with concentrated masses on the fine rods - Mel'nyk, T. A. (Нелінійні коливання, 1999)
Доведенi теореми про збiжнiсть та асимптотичнi оцiнки (коли ε → 0) для власних значень та власних функцiй крайової задачi для оператора Лапласа в плоскому густому перiодичному з’єднаннi з концентрованою масою. Це з’єднання складається з деякої областi i великої кiлько- стi N = O(ε ⁻¹ ) тонких стержнiв. Густина з’єднання є величиною порядку O(ε ^(−α)) на стержнях (концентрацiя маси при α > 0) та O(1) поза стержнями. Можливi три якiсно рiзнi випадки в асимптотичнiй поведiнцi власних значень та власних функцiй: 0 ≤ α < 2, α = 2, α > 2. Головна увага придiляється першому випадку. Convergence theorems and asymptotic estimates (as ε → 0 ) are proved for eigenvalues and eigenfunctions of a boundary value problem for the Laplace operator in a plane thick periodic junction with concentrated masses. This junction consists of the junction’s body and a large number N = O(ε ⁻¹ ) of the fine rods. The density of the junction is order O(ε ^(−α)), α ≥ 0, on the rods (the concentrated masses if α > 0), and O(1) outside of them. There are three qualitatively different cases in the asymptotic behavior of the eigenvalues and eigenfunctions: 0 ≤ α < 2, α = 2, α > 2. The main attention is payed to the case 0 ≤ α < 2.